Medial Meniscal Tears Increase Risk of Moderate to Severe Cartilage Damage to the Medial Femoral Condyle - Campbell, Shannon L.; Franklin, Samuel P. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The objective of this study was to evaluate the relationship between displaceable meniscal tears of the medial meniscus, such as bucket handle tears and flap tears, and articular cartilage wear of the medial femoral condyle.Articular cartilage was scored at the time of arthroscopy and tibial plateau leveling osteotomy as normal, mild, moderately, or severely damaged based on the modified Outerbridge classification system. Dogs with complete cranial cruciate ligament rupture were included; there were 245 stifles in total and 116 had a concurrent displaceable meniscal tear consisting of 115 bucket handle tears and 1 flap tear. Stifles were classified as either having no/mild or moderate/severe cartilage wear. The frequency of moderate/severe wear was compared between stifles with normal menisci and stifles with displaceable meniscal tears using a Fisher's exact test.Stifles with displaceable meniscal tears had a significantly higher frequency of moderate/severe cartilage wear of the medial femoral condyle in comparison to stifles with normal menisci (p = 0.009).These findings suggest that dogs with cranial cruciate ligament rupture and concurrent bucket handle tears may increase the risk of moderate to severe cartilage injury to the medial femoral condyle.
Keywords: cartilage; canine; arthroscopy; cranial cruciate ligament; meniscus